2009
DOI: 10.1007/s12274-009-9059-y
|View full text |Cite
|
Sign up to set email alerts
|

Growth of large-area single- and Bi-layer graphene by controlled carbon precipitation on polycrystalline Ni surfaces

Abstract: We report graphene films composed mostly of one or two layers of graphene grown by controlled carbon precipitation on the surface of polycrystalline Ni thin films during atmospheric chemical vapor deposition (CVD). Controlling both the methane concentration during CVD and the substrate cooling rate during graphene growth can signifi cantly improve the thickness uniformity. As a result, one-or two-layer graphene regions occupy up to 87% of the fi lm area. Single layer coverage accounts for 5 % 11% of the overal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
405
1
4

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 477 publications
(425 citation statements)
references
References 39 publications
15
405
1
4
Order By: Relevance
“…1c) shows the excellent uniformity and 100% surface coverage of the graphene. From the green channel contrast with respect to the underlying SiO 2 /Si substrate in the optical microscope image 12 , we confirmed that all of the graphene area had a single layer, and no multilayer graphene was observed (please also see the RGB colour image in Supplementary Fig. S2).…”
Section: Resultssupporting
confidence: 57%
See 4 more Smart Citations
“…1c) shows the excellent uniformity and 100% surface coverage of the graphene. From the green channel contrast with respect to the underlying SiO 2 /Si substrate in the optical microscope image 12 , we confirmed that all of the graphene area had a single layer, and no multilayer graphene was observed (please also see the RGB colour image in Supplementary Fig. S2).…”
Section: Resultssupporting
confidence: 57%
“…1e). Interestingly, the best reported uniformity over Ni/SiO 2 /Si substrates was only 87% of single-or bilayer graphene 12 . On the popular Cu foils, the best growth results still contain about 5% of thicker-layer graphene 9 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations